Two new species of Thismia (Thismiaceae) from the Brazilian Amazon Forest - Ferreira Da Silva, Diego; Honório, Mayk; Gonçalves Silva, Chirley; A. Teixeira-Silva, Márcia; Silveira, Marcos; Alvarenga Braga, João Marcelo (Phytotaxa, 2023)
Two new species of Thismia (Thismiaceae) from T. subg. Ophiomeris sect. Ophiomeris are described for the Brazilian Amazon Forest, in the Open Ombrophilous Forests of the State of Acre. Here we provide detailed morphological descriptions, with illustrations, distribution maps and preliminary conservation analyses.